2016
DOI: 10.15252/emmm.201606330
|View full text |Cite
|
Sign up to set email alerts
|

Human isotype‐dependent inhibitory antibody responses against Mycobacterium tuberculosis

Abstract: Accumulating evidence from experimental animal models suggests that antibodies play a protective role against tuberculosis (TB). However, little is known about the antibodies generated upon Mycobacterium tuberculosis (MTB) exposure in humans. Here, we performed a molecular and functional characterization of the human B‐cell response to MTB by generating recombinant monoclonal antibodies from single isolated B cells of untreated adult patients with acute pulmonary TB and from MTB‐exposed healthcare workers. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
143
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 56 publications
5
143
2
Order By: Relevance
“…Our study addresses an important point of controversy in the TB field: whether antibodies play a role in immunity against Mtb (20,24), and it also identifies components of this immunity, such as the role for CD4+ T cells. A mechanistic understanding of these issues is critical for the rational as opposed to purely empiric approach for the development of effective preventative and therapeutic TB vaccines.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our study addresses an important point of controversy in the TB field: whether antibodies play a role in immunity against Mtb (20,24), and it also identifies components of this immunity, such as the role for CD4+ T cells. A mechanistic understanding of these issues is critical for the rational as opposed to purely empiric approach for the development of effective preventative and therapeutic TB vaccines.…”
Section: Discussionmentioning
confidence: 90%
“…However, the murine protection assay is both costly and cumbersome and requires a large amount of antibody. In vitro assays using macrophage-mediated killing might identify some protective antibodies (20,24,27), but given the dependence of T-cell immunity for full protection of the antibodies identified by our studies, they may not identify all donors making protective antibodies. We wanted to determine whether the WBA could be used to identify donors who make antibodies that are also protective in the murine assay.…”
Section: Significancementioning
confidence: 90%
See 1 more Smart Citation
“…IgA and IgM responses to a number of M. tuberculosis antigens have been demonstrated in serum from TB patients and individuals with latent M. tuberculosis infection, 8,24,25 and recent findings suggest that different antibody isotypes may differentially affect infection of cells by M. tuberculosis . 26 Further, our experimental methods did not assess antibody glycosylation, the extent of which has been associated with activity in vitro. 27 Finally, we cannot exclude the possibility of classification biases within the consensus case definitions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, human studies have demonstrated that antibodies in LTBI are functionally more competent than antibodies in those with active TB [11,12]. Moreover, active TB is characterized by altered levels of the B cell growth factors, BAFF and APRIL [13], that are crucial factors for peripheral B cell survival and antibody production [14].…”
Section: Introductionmentioning
confidence: 99%